The SIMBA User Alert Service Architecture for Dependable Alert Delivery - Bahl, Paramvir; Russell, Wilf; Wang, Yi-Min; Bahl, Victor (Institute of Electrical and Electronics Engineers, Inc., 2001)
Alerts refer to the delivery of user-subscribed information to the user. As the number of alert services and the types of information delivery devices increase, a new model that allows users to manage alert delivery and avoid alert overflow is needed. The unique dependability challenge in the management of alerts is in the proper use of redundancy to achieve timeliness and reliability without being unduly intrusive or cumbersome. We describe the design, implementation, and user experience of an alert service architecture, called SIMBA. SIMBA utilizes Instant Messaging with acknowledgements as the universal, reliable alert delivery channel, with emails being the fallback channel. All alerts that a user subscribes to are first directed to the user’s MyAlertBuddy, which allows centralized delivery preference customization and acts as a personal alert router to protect the privacy of user addresses. Delivery modes, each of which involves multiple user addresses to accommodate communication failures, are supported as an abstraction for specifying personalized dependability levels. A working implementation of the SIMBA system, which integrates five different types of alert services, is described. Challenges and techniques in maintaining a highly available MyAlertBuddy to avoid single-point of failure are discussed. The concept of exception-handling automation is introduced for enhancing the robustness of applications that drive third-party communication client software through automation interfaces.